Direct Ink Writing: A 3D Printing Technology for Diverse Materials. Issue 28 (28th April 2022) - Saadi, M. A. S. R.; Maguire, Alianna; Pottackal, Neethu T.; Thakur, Md Shajedul Hoque; Ikram, Maruf Md.; Hart, A. John; Ajayan, Pulickel M.; Rahman, Muhammad M.
Abstract: Additive manufacturing (AM) has gained significant attention due to its ability to drive technological development as a sustainable, flexible, and customizable manufacturing scheme. Among the various AM techniques, direct ink writing (DIW) has emerged as the most versatile 3D printing technique for the broadest range of materials. DIW allows printing of practically any material, as long as the precursor ink can be engineered to demonstrate appropriate rheological behavior. This technique acts as a unique pathway to introduce design freedom, multifunctionality, and stability simultaneously into its printed structures. Here, a comprehensive review of DIW of complex 3D structures from various materials, including polymers, ceramics, glass, cement, graphene, metals, and their combinations through multimaterial printing is presented. The review begins with an overview of the fundamentals of ink rheology, followed by an in‐depth discussion of the various methods to tailor the ink for DIW of different classes of materials. Then, the diverse applications of DIW ranging from electronics to food to biomedical industries are discussed. Finally, the current challenges and limitations of this technique are highlighted, followed by its prospects as a guideline toward possible futuristic innovations. Abstract : The comprehensive review comprises recent development in direct‐ink‐writing (DIW) 3D printing technology for the development of 3D structures from various materials such as polymers, ceramics, glass, cement, graphene, metals, and multimaterials. The work describes the fundamentals and engineering of ink rheology required for DIW. In addition, a multitude of applications, current challenges, and future prospects of the technology are discussed.